PENDIDIKAN PLURALISME AGAMA (MEMBANGUN HUBUNGAN SOSIAL LINTAS AGAMA DI SEKOLAH) - Sapendi, Sapendi (The Pontianak State Institute of Islamic Studies, 2012)
Lately, religion has become something scary and worrying. Religion in the hands of its followers often appears with a violent face and seems to have lost its friendliness. In recent years, there have been a lot of conflicts, intolerance and violence in the name of religion and belief in various regions in Indonesia. In the context, it becomes reasonable when certain people call religion the source of the problem in the world. The religious views that tend to be anachronistic potentially leads to conflict. In fact, to say that religion is a source of problem is clearly not wise and unhistorical, due to the fact for centuries, religion has given contribution to millions of people. In the context of eliminating the destructive aspects of religion and presenting constructive side of it as a unifying factor, schools as an institution mandated to educate the nation should take part in providing an understanding of religion and should be capable of creating an environment that provides educational opportunities to students to construct harmonious social relations between students of different religion.